2012
DOI: 10.1088/0954-3899/39/10/105001
|View full text |Cite
|
Sign up to set email alerts
|

Possible interpretation of theZb(10610) andZb(10650) in a chiral quark model

Abstract: Abstract. Motivated by the two charged bottomonium-like resonances Z b (10610) and Z b (10650) newly observed by the Belle collaboration, the possible molecular states composed of a pair of heavy mesons, BB, BB * , B * B * , B sB , etc (in S-wave), are investigated in the framework of chiral quark models by the Gaussian expansion method. The bound states BB * and B * B * with quantum numbers I(J P C ) = 1(1 +− ), which are good candidates for the Z b (10610) and Z b (10650) respectively, are obtained. Other th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
37
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 45 publications
(68 reference statements)
1
37
0
Order By: Relevance
“…The authors in Ref. [6] further showed that their quantum numbers are I(J P ) = 1(1 + ). The QCD sum rule (QSR) analysis that was developed by Zhang et al [9] suggested that Z b (10610) could be a BB * molecular state.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The authors in Ref. [6] further showed that their quantum numbers are I(J P ) = 1(1 + ). The QCD sum rule (QSR) analysis that was developed by Zhang et al [9] suggested that Z b (10610) could be a BB * molecular state.…”
Section: Introductionmentioning
confidence: 95%
“…The heavy quark spin structure that was developed by Bondar et al [5], the chiral constituent quark model approach in Ref. [6], the effective Lagrangian approach via the one-boson exchange in Ref. [7], and the study of the line shape in the vicinity of B ( * )B( * ) thresholds, as well as two-body decay rates using effective field theory in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…The Z b (10610) and Z b (10650) appear near the BB * and B * B * thresholds, respectively. It is natural to relate the Z b (10610) and Z b (10650) with the BB * and B * B * molecular states, respectively [24][25][26][27][28][29][30][31][32][33][34][35][36]. Other assignments, such as the tetraquark states [37][38][39], threshold cusps [40], the re-scattering effects [41,42], etc.…”
Section: Introductionmentioning
confidence: 99%
“…In 2013, the Belle collaboration reported the first observation of the decay processes ϒ(5S) → ϒ(1, 2, 3S) π 0 π 0 , and they obtained the neutral particle Z 0 b (10610) in a Dalitz analysis of the decays to ϒ(2, 3S) π 0 [14]. There have been several assignments of the Z b (10610) and Z b (10650), such as the molecular states [15][16][17][18][19][20][21][22][23][24][25], tetraquark states [26,27], threshold cusps [28], rescattering effects [29,30], etc.…”
Section: Introductionmentioning
confidence: 99%